Examining The Perception of Emotional Facial Expressions in Early Childhood - Lee, Vivian (My University, 2016)
Adults perceive basic emotional facial expressions as discrete categories using categorical perception. Within categorical perception, discrimination of facial emotional expressions is better for between category faces than within category faces. In this thesis, I examined the developmental trajectory of categorical perception in early childhood. I also examined the relationship between sensitivity to physical differences in facial emotional expressions and the use of emotion labels in toddlers. In Chapter 2, I found that infants before 12-months failed to discriminate between category faces along a happy-sad continuum. In contrast, evidence suggest that 9- and 12-month old infants categorically perceived faces along a happy-angry continuum. These findings suggest that categorical perception may not develop concurrently for all emotions. In Chapter 3, I found that toddlers by 26-months of age categorically perceived faces along a happy-sad continuum. These results highlight the long developmental trajectory of categorical perception of facial emotional expressions across early childhood. In Chapter 4, I found a relationship between perceptual sensitivity to physical differences between happy and sad faces, and the emotion vocabulary size in 26-month-olds. This relationship suggests that learning about emotions may utilize information from multiple domains, and that learning in one domain may influence the development of another. The perception of facial emotional expressions is an essential component of early social emotional development. Categorical perception is a mechanism that aids in organizing complex social information from faces into actionable categories. The research in this thesis advances our understanding of early social perceptual development and the process that allow us to successfully navigate in the social world.
Keywords: Face Perception; Emotions; Categorical Perception; Emotion Understanding; Child Development; Visual Development